Translating Cultural References in Tourism Discourse: the Case of the Apulian Region (Altre Modernità, 2012)
The aim of this paper is to provide a reflection on cultural references in tourism discourse, highlighting the difficulties translators may face when dealing with culture-bound words (Newmark 1988: 95-102; Katan 1999: 45-65; Oltra Ripoll 2005: 76-78). On the basis of a corpus of texts belonging to different genres, this study will investigate how the lexical features described by G. Dann in terms of languaging (1996: 183) are differently displayed and distributed, and whether a different rate of languaging could be said to enhance or detract from the communicative effectiveness of the selected texts: a guidebook, a monograph and five tourist brochures about the Southern Italian region of Apulia. Some of the most relevant translation choices will be reflected upon, showing how different communicative strategies are at work and end up producing “a different emphasis and degree of explanation” (Poncini 2006: 145) in the foreign tourists’ comprehension of Apulian cultural references.